A Consuequence of Satisfaction and Loyalty: How Waterpark Images and Price Fairness Affect its: An Empirical Study of Bengkulu - Fachri Eka Saputra; Fedyah Anggriani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
The purpose of this study as to determine how the effect of waterpark image and price fairness on customer satisfaction and its implications for customer loyalty at Waterpark Wahana Surya Bengkulu. The measurement of this study uses 14 indicator items which are distributed using an online questionnaire. The number of samples in this study were 136 respondents and the data were analyzed using SEM PLS (Partial Least Square). Date were collected using a questionnaire using a Likert scale. This research used descriptive method with a quantitative approach. The type of data used in this study is primary data. The results of this study prove that 1. waterpark image has a positive effect on price fairness, 2. Waterpark image has a positive effect on customer satisfaction, 3. Fairness of price has a positive effect on customer satisfaction, 4. Waterpark image has a positive effect on customer loyalty, 5. Fairness of price has a positive effect on customer loyalty, 6. Customer satisfaction has no effect on customer loyalty.